(untitled) (Research, Society and Development, 2020)
Spinal muscular atrophy (EBF) is a specific type of neuromuscular disease, caused by the degeneration of motor neurons, resulting in atrophies and progressive muscle weakness. The use of drugs associated with rehabilitation seeks to provide more quality of life for the individual and the family. The objective was to verify the level of perception of families of patients with EBF regarding the effectiveness of using the Spinraza® medication associated with physical therapy. This is a cross-sectional, quantitative and qualitative study, carried out using an online form sent to the families of individuals with EBF from all over Brazil, who answered a semi-structured questionnaire with questions related to the use of the medication Spinraza® and the physiotherapeutic treatment. . Descriptive statistics was performed. 114 families participated, of which 60% had individuals using the drug. Regarding physical therapy treatment, only 1 child does not follow up with this professional. Most family members (53%) pointed out that they noticed greater advances in the treatment with physical therapy associated with the use of the medication and 8% of these believe that only physical therapy is enough. It is concluded that the relatives of individuals with EBF present a positive perception of improvement in their clinical condition when they use the medication Spinraza® associated with physical therapy. In this sense, the combination of both treatment approaches should be without incentives to prevent the progression of EBF, providing a better quality of life for the individual and the family.